Bagian Mutlak ( Legitime Portie ) Ahli Waris Berbagai Golongan Menurut Hukum Perdata Dan Kompilasi Hukum Islam - Siti Rahmah; Hamdan Khairul Mubarak; Muhammad Al Mansur (Lembaga Pengembangan Kinerja Dosen, 2023)
In the Civil Code concerning civil inheritance law it is classified as one of the aspects of civil law which has the basic meaning contained therein, namely to regulate but there is no element of demand in this matter. Whatever the heir does to his property before he dies is his power, and that is part of the civil law that is regulatory. Inheritance law is the law that controls the locking of inheritance that is freed because the owner has died, and its effect on the person entitled to receive the inheritance. There are two ways to obtain inheritance, namely: based on statutory provisions or ab intestato wettelijk erfrecht, and appointed in a will or testamentair erfrecht). The problem is how to implement the absolute portion (legitime portie) of the heirs of various groups according to civil law laws. This paper uses library research methods in the form of books, scientific journals, magazines, and so on. legitieme fortie (absolute part) is part of the inheritance or inheritance which must be divided among the heirs in a straight line downwards and upwards, and regarding which part the heirs prevent from deciding something either in the form of a grant (gift) or in the form of a testamentary grant (Article 913 KHU civil). Asser Meyyers argues about inheritance law in the Netherlands page 148 explaining that the purpose of legimie portie is to avoid and protect the heir from the desire that arises for the heir to benefit other people.